The application of breath-holding in sports: physiological effects, challenges, and future directions - Elia, A.; Lemaître, F. (European Journal of Applied Physiology, 2025)
Repeated breath-holding has been shown to elicit transient increases in haemoglobin and erythropoietin concentrations, while long-term engagement in breath-hold-related activities has been linked with improved hypercapnic tolerance, mental resilience, and favourable cardiorespiratory, cerebrovascular, and skeletal muscle adaptations. Given these findings, breath-holding was proffered as a possible performance optimisation strategy a little over a decade ago. This prompted practitioners and researchers to explore its broader application either as a priming strategy completed immediately before an endurance activity or as an alternative hypoxic-hypercapnic training method. Therefore, this review aims to offer an update of the acute and long-term physiological responses to breath-holding that are relevant to athletic performance and provide an overview of the existing body of knowledge surrounding its potential utility and efficacy as a performance enhancement strategy. Current evidence suggests that breath-holding may have potential as a priming strategy; however, further placebo-controlled studies are required to rigorously evaluate its efficacy. Additionally, it is evident that developing an effective protocol and administering it successfully is more complex than initially thought. Key factors such as the characteristics of the prescribed protocol, the timing of the intervention relative to the event, and the nature of the existing warm-up routine all require careful consideration. This highlights the need for adaptable, context-specific approaches when integrating breath-holding into real-world sporting environments. Finally, while dynamic breath-hold training shows the greatest potency as a performance optimisation strategy, further research is necessary to determine the optimal training protocol (i.e., hypoxaemic-hypercapnic dose), and duration.